Development of Canva Based Educational Games on the Material of the Meaning of the Pancasila Principles in Society for Grade IV Elementary School Students - Angel Marselina Tamba; Zaka Hadikusuma Ramadan (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to develop a Canva based educational game on the material of the meaning of the Pancasila principles in society for grade IV Elementary School students. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, but is limited to the Development stage. The study was conducted at State Elementary School 167 Pekanbaru. Data collection techniques include interviews, product validation by linguists, material experts and media experts, as well as response tests from teachers and students. Data analysis was carried out qualitatively and quantitatively. The results of this study indicate that the Canva-based educational game is declared valid without revision. Based on the validation results from linguists 92%, material experts 99% and media experts 91% with the criteria "Very Valid". While the percentage of values ​​​​generated from teacher responses is 100% and student responses 97% with the category "Very Practical". Based on the results of the study, the learning media developed is very feasible and practical to use as a learning medium for the material of the meaning of the Pancasila principles in society for grade IV Elementary Schools.